2013
DOI: 10.1186/1810-522x-52-49
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monsoon-driven hydrographic features on thaliacean distribution in waters around Taiwan, western North Pacific Ocean

Abstract: Background: The mesoscale distribution of thaliaceans associated with hydrographic conditions in the waters around Taiwan was investigated during two different monsoon seasons in 2004 in order to elucidate possible influences of hydrological conditions driven by seasonal monsoons on distributional patterns of thaliaceans. Results: In total, 18 thaliacean species, belonging to 12 genera and 3 families, were identified in our samples. Thalia rhomboides, Doliolum denticulatum, Doliolum nationalis, Thalia oriental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
2
7
0
1
Order By: Relevance
“…During the survey period, the species identified in the northeastern East China Sea were similar to those found in the neighboring waters of Northeast Asia (Table 5). The list of salps and doliolids from countries neighboring South Korea includes a total of 30 species across 13 genera, including 13 species identified in our study [3,15,16,[43][44][45][46]. Particularly, we confirmed that doliolid species such as Dolioletta gegenbauri, Doliolum denticulatum, and Doliolum nationalis and salp species such as Cyclosalpa affinis, Salpa fusiformis, Thalia cicar, T. orientalis, and T. sibogae are commonly distributed around South Korea, China, Japan, and Taiwan (Table 5).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…During the survey period, the species identified in the northeastern East China Sea were similar to those found in the neighboring waters of Northeast Asia (Table 5). The list of salps and doliolids from countries neighboring South Korea includes a total of 30 species across 13 genera, including 13 species identified in our study [3,15,16,[43][44][45][46]. Particularly, we confirmed that doliolid species such as Dolioletta gegenbauri, Doliolum denticulatum, and Doliolum nationalis and salp species such as Cyclosalpa affinis, Salpa fusiformis, Thalia cicar, T. orientalis, and T. sibogae are commonly distributed around South Korea, China, Japan, and Taiwan (Table 5).…”
Section: Discussionsupporting
confidence: 78%
“…Pelagic thaliaceans (salps, doliolids, and pyrosomes) are planktonic, gelatinous zooplankton belonging to the phylum Chordata. These organisms are filter feeders that consume phytoplankton of various sizes in marine ecosystems [1][2][3]. Salps and doliolids exhibit a unique life cycle that alternates between asexual and sexual reproduction to maintain their population [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perissinotto et al (2007) found higher retention efficiencies for cells greater than 10 μm in P. atlanticum, and fatty acids indicated a mixed phytoplankton diet of diatoms, dinoflagellates, and prymnesiophytes. P. atlanticum carcasses also contribute to carbon export, which can be substantial following blooms (Lebrato and Jones 2009;Liao et al 2013).…”
mentioning
confidence: 99%
“…3D). Hereu et al 2006;Liao et al 2013). Indian Ocean (Godeaux 1980;Godeaux 1974;1997;Weikert & Godeaux 2008;Batistić et al 2014).…”
Section: Resultsunclassified